Oxidative removal of oxytetracycline by UV-C/hydrogen peroxide and UV-C/peroxymonosulfate: Process optimization, kinetics, influence of co-existing ions, and quenching experiments - Varank, Gamze; Can-Guven, Emine; Guvenc, Senem Yazici; Garazade, Narmin; Turk, Oruc Kaan; Demir, Ahmet; Cakmakci, Mehmet (ELSEVIER, 2022)
Oxytetracycline (OTC) is a tetracycline group antibiotic with high environmental pollution potential and is resistant to conventional treatment processes. This study provides an environmentally friendly and efficient OTC treatment by ultraviolet (UV)-based advanced oxidation processes. UV irradiation was used for the activation of hydrogen peroxide (HP) and peroxymonosulfate (PMS). In the first stage of the study, control experiments were conducted and the effect of initial pH on the UV/HP and UV/PMS in OTC removal was evaluated. In the following part, variables of the UV/HP and UV/PMS were optimized by the Box-Behnken design. The optimum conditions of the UV/HP process were as follows: 6.5 mg/L initial OTC concentration, 3.50 mM HP dose, and 45.4 min reaction time. The optimum parameters of the UV/PMS process were: 5 mg/L initial OTC concentration, 3.69 mM PMS dose, and 42.75 min reaction time. 72.8 % and 50.96 % OTC removal efficiency were achieved with the validation experiments by the UV/PMS and UV/HP processes, respectively. Kinetic studies showed that Cl- and HCO3- ions have a positive effect whereas SO42- has a negligible effect on the reaction rate of both processes. NO3- has a positive effect on the UV/HP process and a negligible effect on the UV/PMS process. According to the radical scavenging experiments, hydroxyl radicals were dominant in the UV/HP process while in the UV/PMS process both hydroxyl and sulfate radicals were involved. Both processes were effective in OTC removal; however, the UV/PMS process is more efficient and cost-effective.
Keywords: Tetracycline; Ultraviolet; Box-Behnken design; Water matrix; Radical scavengers; MUNICIPAL WASTE-WATER; MEDIUM PRESSURE UV; AQUEOUS-SOLUTION; PHOTOCHEMICAL DEGRADATION; TETRACYCLINE ANTIBIOTICS; PEROXYMONOSULFATE; ACTIVATION; PERSULFATE; UV/H2O2; SULFATE; Engineering; Water Resources